GERBEK JENTIK: RALLY THE SPIRIT OF COMMUNITY COLLABORATION TO FIGHT MOSQUITOES! GERBEK JENTIK: BANGKITKAN SEMANGAT KOLABORASI WARGA LAWAN NYAMUK! - Arshy Prodyanatasari; Adi Laksono; Ananda Ika Trisnamwati; Wahyu Sri Astutik; Putu Daneswara Widodo; Nurul Hidayah (PT. ROCE WISDOM ACEH, 2026)
Dengue Hemorrhagic Fever (DHF) remains a serious health problem in Indonesia, with cases increasing by 40% in early 2025 compared to the previous year. Wates Village, Kediri Regency, is an endemic area with the lowest Larva-Free Index (LFI) in the district (45%), necessitating comprehensive community-based intervention. The GERBEK JENTIK program aims to enhance public knowledge of DHF prevention, establish jumantik (larva monitor) cadres, and reduce larva indices through a participatory approach. Activities were carried out in three stages: (1) Interactive education and socialization; (2) Collaborative training between the community and jumantik cadres; (3) Practical demonstration of larva inspection and mass clean-up movement. The participants consisted of 46 residents of Wates Village. The program significantly improved public understanding, formed competent jumantik cadres, and reduced the larva index from 45% to 78%. Collaboration among health workers, cadres, and the community proved effective in creating sustainable change. The GERBEK JENTIK program is effective in addressing DHF through a collaborative approach. Recommendations include integrating the program into village policy, replicating the model in other endemic areas, developing a digital monitoring system, and providing ongoing mentoring every 3-6 months.